The Effect of Product Quality and Service Quality on Repurchase Intention with Customer Satisfaction as a Mediation Variables (Case Study on CV. Prima Anugerah Sejati) - Fath Arif Mukti Sukaeri; Budi Santoso; Agung Dharmawan Buchdadi (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2023)
This study aims to analyze the effect of product quality and service quality on repurchase intention with customer satisfaction as a mediating variable. population of customers Printing CV. Prima Anugerah Sejati as many as 372 in December 2020. This study used 36 indicators, so that using an estimate based on the number of indicators obtained a sample size of around 180 respondents. Interval data in this study were generated using the Agree-Disagree Scale technique by developing statements that produce agree-disagree answers in various ranges of values ​​(Ferdinand, 2014: 160).The testing of the hypothesis in this study uses the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS).The research results indicate that 1)product qualityhas a positive and significant effect on customer satisfaction, indicating that if the quality of the product offered is getting better, customer satisfaction will increase.2) quality of servicehas a positive and significant effect on customer satisfaction, indicating that if the quality of service provided is getting better, customer satisfaction will increase. 3) customer satisfaction is able to significantly mediate the effect of product quality on repurchase intention, indicating that customer satisfaction is a factor that can significantly increase the effect of product quality on repurchase intention. 4) customer satisfaction is able to significantly mediate the effect of service quality on repurchase intention, customer satisfaction is a factor that can significantly increase the effect of service quality on repurchase intention.